2012
DOI: 10.1074/jbc.m111.313692
|View full text |Cite
|
Sign up to set email alerts
|

A Pivotal Heme-transfer Reaction Intermediate in Cytochrome c Biogenesis

Abstract: Background: Heme attachment to cytochrome c is a catalyzed post-translational modification.Results: We identify a ternary complex of the cytochrome c biogenesis protein CcmE, heme, and a cytochrome, and demonstrate its functional significance.Conclusion: The complex is a trapped catalytic intermediate at the point of heme transfer from the cytochrome biogenesis apparatus to the cytochrome.Significance: An insight into biosynthesis of heme proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…2C). A similar, highly stable holoCcmE dimer has been reported previously (18,24), and our data with the apoCcmE derivative indicated that the presence of heme is not required for this oligomerization.…”
Section: Heterologous Expression and Purification Of Apoccme And Apocsupporting
confidence: 90%
See 3 more Smart Citations
“…2C). A similar, highly stable holoCcmE dimer has been reported previously (18,24), and our data with the apoCcmE derivative indicated that the presence of heme is not required for this oligomerization.…”
Section: Heterologous Expression and Purification Of Apoccme And Apocsupporting
confidence: 90%
“…The heme was covalently ligated to both CcmE and apocytochrome b 562 variant via the His and Cys residues, respectively. A similar complex was also obtained in vitro using the Hydrogenobacter thermophilus apocytochrome c 552 (18).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Recent progress has been made in establishing the functional relevance of the covalent bond, which is between a histidine N and the b-carbon of one of the heme vinyl groups (45). A complex between the membrane-anchored CcmE and a variant cytochrome c was trapped in vivo and characterized (46). The effects on the formation of the complex caused by changes in the other Ccm proteins indicate that the covalent bond is on-pathway and physiologically relevant.…”
Section: Heme Transport and Provisionmentioning
confidence: 99%